Nutrition knowledge, diet quality and orthorexic behaviors in Polish students-a pre-post repeated cross-sectional study. - Marta Plichta; Marzena Jezewska-Zychowicz (PLoS ONE)
Nutrition knowledge acquired in college students may not only help in promoting an adequate diet, but also lead to excessive preoccupation with healthy eating, which is referred to as orthorexic behaviors. This study aimed to assess the relationship between nutrition knowledge, diet quality and orthorexic behaviors among college students of food and nutrition majors. Data were collected from a sample of 131 college students through a pre-post repeated cross-sectional study conducted from 2018 to 2021. The participants were asked to complete the ORTO-6 questionnaire, the nutrition knowledge test "GAROTA", and the Beliefs and Eating Habits Questionnaire (KomPAN). The results indicated that students' preoccupation with healthy eating (orthorexic behaviors score) during the study period did not change, in contrast nutrition knowledge and diet quality increased. There was no correlation between the orthorexic behaviors score and the nutrition knowledge score, both at the beginning and end of the study. At the beginning of the study, the orthorexic behaviors score correlated positively with "Pro-Healthy Diet Index" and "Diet-Quality Index", and inversely with "Non-Healthy Diet Index". However, at the end of the study, no significant correlations were observed between these variables. It can be concluded that nutrition knowledge determined positively the quality of the diet of students in food and nutrition majors, while did not affect the occurrence of orthorexic behaviors.